2016
DOI: 10.3324/haematol.2015.140368
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells from pooled mononuclear cells of multiple bone marrow donors as rescue therapy in pediatric severe steroid-refractory graft-versus-host disease: a multicenter survey

Abstract: © Ferrata Storti Foundation IntroductionSince the first clinical trial of mesenchymal stromal cells (MSC) 9,10 Another important issue regarding the clinical application of MSCs is their culture under serum-free conditions. The majority of clinical studies have used MSCs that were expanded in media supplemented with fetal bovine serum (FBS). 1,[11][12][13][14][15] To avoid the risks associated with the use of FBS, 16 platelet lysate (PL) was proposed as a supplement to tissue culture media for MSCs. 17 Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
83
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 41 publications
1
83
1
3
Order By: Relevance
“…Also, treatment with CM or 10× CM led to considerable increase in synthesis of basal levels of extracellular matrix component like elastin which is a key protein responsible for skin tightening and retention of skin elasticity. In a study published earlier, it has been documented that CM from adipose tissue has a similar effect on dermal fibroblast [17]. In addition, our BMMSC CM was able to restore the viability and ECM integrity following the induction of oxidative stress and UV-B damage.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Also, treatment with CM or 10× CM led to considerable increase in synthesis of basal levels of extracellular matrix component like elastin which is a key protein responsible for skin tightening and retention of skin elasticity. In a study published earlier, it has been documented that CM from adipose tissue has a similar effect on dermal fibroblast [17]. In addition, our BMMSC CM was able to restore the viability and ECM integrity following the induction of oxidative stress and UV-B damage.…”
Section: Discussionmentioning
confidence: 70%
“…The rationale for using a three donor pool of BMMSC as opposed to a single donor derived cells relates to the fact that MSCs including BMMSC from different donors show significant variability in their proteomic signature which may eventually be manifested in the composition of the CM [17] [18] [19]; and one of the ways to minimize this problem would be to use a pooled population of MSCs for CM production. In this communication, we report that this medium is highly enriched in factors that are known to stimulate cell proliferation and migration, angiogenesis, remodeling of ECM and re-epithelialization, and a combination of such diverse macro-and small molecules may inversely modulate the skin aging process.…”
Section: Introductionmentioning
confidence: 99%
“…Generated MSCs were frozen in 209 vials and labeled as an MSC bank. This novel manufacturing protocol is characterized by high potency and near-identity of individual doses, termed MSC-Frankfurt am Main (MSC-FFM) [24]. Recently, Bader et al [5] reported outcomes of 69 adult and pediatric patients who received a total of 212 doses of MSC-FFM for therapy-refractory aGvHD in a routine clinical setting in 23 allogeneic transplant centers from 6 countries.…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 99%
“…Certain factors, including skin involvement and lower aGvHD grade, yielded a higher response rate to MSC application [25]. Possibly, inconsistent results of clinical studies are attributable to different or inconsistent pharmacological quality of MSCs resulting from the lack of a standardized methodology for MSC generation, dosing, and interdonor heterogeneity [5, 24]. Kuçi et al [24] developed a novel approach for MSC generation from pooled bone marrow mononuclear cells of 8 allogeneic, third-party donors to overcome donor-to-donor variability.…”
Section: Mscs In the Treatment Of Agvhdmentioning
confidence: 99%
“…Additionally, our choice to pool samples may reflect a more clinically-relevant application of MSCs. For example, it has been proposed that pooled donor samples may be advantageous in overcoming the heterogeneity associated with the efficacy of MSC-based therapies (Kuçi et al, 2016). Thus, while we lose individual variance from pooling cells from different genetically identical donors, we gain an understanding of how an at-risk population may be influenced by environmental contaminants.…”
Section: Discussionmentioning
confidence: 99%